2012
DOI: 10.1164/rccm.201108-1562oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung 18F-Fluorodeoxyglucose Positron Emission Tomography for Diagnosis and Monitoring of Pulmonary Arterial Hypertension

Abstract: Rationale: Pulmonary arterial hypertension (PAH) is a proliferative arteriopathy associated with glucose transporter-1 (Glut1) up-regulation and a glycolytic shift in lung metabolism. Glycolytic metabolism can be detected with the positron emission tomography (PET) tracer 18 F-fluorodeoxyglucose (FDG).Objectives: The precise cell type in which glycolytic abnormalities occur in PAH is unknown. Moreover, whether FDG-PET is sufficiently sensitive to monitor PAH progression and detect therapeutic regression is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(202 citation statements)
references
References 36 publications
7
193
1
1
Order By: Relevance
“…One week after induction of PAH with MCT, a time point that corresponds to the onset of detectable pulmonary vascular disease but early in the course of evolution of PAH,21, 22 rats were treated with intraperitoneal injections of 0.5 mg/kg filter‐sterilized colchicine (Sigma‐Aldrich, St. Louis, MO) dissolved in PBS (n=24) or an equivalent volume of PBS (n=28) on Monday, Wednesday, and Friday for 3 weeks and were then analyzed. A sample size of 25 to 30 was targeted for 3 reasons: there were 3 groups in the analysis, to reduce effects of the heterogeneity with colchicine treatment, and to account for possible deaths during the experimental time frame.…”
Section: Methodsmentioning
confidence: 99%
“…One week after induction of PAH with MCT, a time point that corresponds to the onset of detectable pulmonary vascular disease but early in the course of evolution of PAH,21, 22 rats were treated with intraperitoneal injections of 0.5 mg/kg filter‐sterilized colchicine (Sigma‐Aldrich, St. Louis, MO) dissolved in PBS (n=24) or an equivalent volume of PBS (n=28) on Monday, Wednesday, and Friday for 3 weeks and were then analyzed. A sample size of 25 to 30 was targeted for 3 reasons: there were 3 groups in the analysis, to reduce effects of the heterogeneity with colchicine treatment, and to account for possible deaths during the experimental time frame.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that stimulating GO via FAO inhibition may be an effective pharmacological approach to improve cardiac function and efficiency, however a limited number of studies have thoroughly studied this in animal PAH models (Ussher et al, 2009;Sutendra et al, 2010;Marsboom et al, 2012). The Randle cycle may be exploited therapeutically by shifting the primary fuel source from FAs and stimulating GO.…”
Section: Randle Cyclementioning
confidence: 99%
“…There is increasing evidence that pathologic remodeling of the pulmonary vasculature is associated with abnormal cellular metabolism and studies with patients and animals have shown increased lung uptake with FDG PET (Hagan et al, 2011;Marsboom et al, 2012;Zhao et al, 2013;Ryan et al, 2013) Two studies using the monocrotaline rat model of severe PAH have shown that increased accumulation of FDG tracer may be detected in lung parenchyma and that there is an associated increased expression of GLUT1 and other glycolytic proteins Zhao et al, 2013) . Marsboom's group demonstrated that elevated lung FDG signals may be detected during early, mild PAH and that the signal progressively increases with evolving PAH.…”
Section: Lung Changes In Metabolismmentioning
confidence: 99%
See 2 more Smart Citations